The basics of digital forensics the primer for getting started in digital forensics - Sammons, John (The basics, 2012)
The Basics of Digital Forensics provides a foundation for people new to the digital forensics field. This book teaches you how to conduct examinations by discussing what digital forensics is, the methodologies used, key technical concepts and the tools needed to perform examinations. Details on digital forensics for computers, networks, cell phones, GPS, the cloud, and Internet are discussed. Also learn how to collect evidence, document the scene, and how deleted data is recovered. Learn all about what Digital Forensics entails Build a toolkit and prepare an investigative plan Understand the common artifacts to look for during an exam